Ecological implications of the pink salmon invasion in northern Norway—Aggregative responses and terrestrial transfer by white‐tailed eagles - Bror Mathias Bonde; Audun Stien (Ecology and Evolution)
Abstract Over the last 10 years, the spawning population of invasive pink salmon (Oncorhynchus gorbuscha) has increased in the river systems in northern Norway to a level that is causing concern about their impact on endemic fauna and ecosystem processes. The scale of transfer of pink salmon carcasses into the terrestrial ecosystem is likely to be a key determinant of terrestrial impact. Bears (Ursus sp.) are responsible for most such transfers in North America but are rare in Norway. The white‐tailed eagle (Haliaeetus albicilla) is common however, and a candidate to be a main cause of such transfers. To evaluate this hypothesis, data on the abundance of white‐tailed eagles and pink salmon were collected along the river Skallelv in northern Norway in 2021, a year the pink salmon spawned in the river, and in 2022, a year no pink salmon spawned in the river. The abundance of white‐tailed eagles along the river was much higher the year pink salmon spawned in the river. Furthermore, white‐tailed eagles were observed aggregating and catching pink salmon where and when pink salmon were present at the spawning and post‐spawning stages. Based on our observations, we suggest that the white‐tailed eagle is the main species involved in the transport of pink salmon from the river into the riparian zone in northern Norway and that other scavengers, in particular the red fox (Vulpes vulpes) and common raven (Corvus corax), play an important role in transporting pink salmon carcasses from the riparian zone to the wider terrestrial ecosystem.